RNAsnp: Efficient Detection of Local RNA Secondary Structure Changes Induced by SNPs. Issue 4 (20th March 2013) - Sabarinathan, Radhakrishnan; Tafer, Hakim; Seemann, Stefan E.; Hofacker, Ivo L.; Stadler, Peter F.; Gorodkin, Jan
<x xml:space="preserve">Abstract</x> Structural characteristics are essential for the functioning of many non‐coding RNAs and cis‐regulatory elements of mRNAs. Predictions of the significance of sequence variants on structural effects were made using RNAsnp on a dataset of 30 known SNPs reported to have a structural effect. The four experimentally validated SNPs were correctly predicted with this application (p‐value < 0.1). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>